INDONESIAN GOVERNMENT CHALLENGES IN RATIFICATION OF THE INTERNATIONAL CONVENTION ON REFUGEES - Muhammad Abdul Aziz Putra Andistan; Achmad Zulfikar (Jisiera: The Journal of Islamic Studies and International Relations, 2018)
War and conflict lead to situations that are not conducive, so that people choose to leave their country and move to another country that is considered more secure and worthy to live in. These people are called refugees and the number has reached 60 million in the world. Indonesia is part of the refugee journey. However, Indonesia has not been a party to the 1951 Convention and the 1967 Protocol on Refugees. This underlies the research objectives for analyzing the challenges of the Indonesian government to ratify the International Convention on Refugees. Qualitative research methods are used to develop interpretation and data collection from the literature review. The study finds that the challenges of Indonesian government to ratify the International Convention on Refugees are due to economic challenges in fulfilling the obligations to refugees, security challenges that potentially open transnational crime opportunities, and international practice challenges that demonstrate non-compliance by the Convention's receiving countries in their countries